Promoting the health and well-being of English-speaking Seniors in Quebec. A community model (infographic) - Community Health And Social Services Network/Réseau communautaire de santé et de services sociaux (2019)
fs-ref-orig: Community Health And Social Services Network. (2019). Promoting the health and well-being of English-speaking Seniors in Quebec. A community model [infographic]. fs-code-orig: Community Health And Social Services Network-2019

Promoting the health and well-being of English-speaking seniors in Quebec. A community model - Kueber, Rusell (Community Health and Social Services Network, 2019)

Promotion de la santé et du bien-être des aînés d’expression anglaise du Québec : un modèle communautaire - Kueber, Russell (Réseau communautaire de santé et de services sociaux, 2019)

Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire( infographie) - Réseau communautaire de santé et de services sociaux/Community Health and Social Services Network (2019)
fs-ref-orig: Réseau communautaire de santé et de services sociaux. (2019). Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire [infographie]. fs-code-orig: Réseau communautaire de santé et de services sociaux-2019

Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Anglophone Magdalen Islanders, 2018)
fs-ref-orig: Richardson, M. et Ledoux, J.-J. (2018). Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes. Council for Anglophone Magdalen Islanders. fs-code-orig: Richardson-2018

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.